THE IMPACT OF COVID-19 PANDEMIC ON ORGANIZATIONAL CULTURE AND ORGANIZATIONAL COMMITMENT OF THE EMPLOYEES OF MULTILEVEL MARKETING COMPANY IN AMBON CITY - Saleh Tutupoho; Latuihamallo Juliana; Pieter N. R. Rehatta (Manis: Jurnal Manajemen dan Bisnis, 2021)
The Corona Virus Disease 2019 (COVID-19) pandemic has had a huge impact on changes around the world, including on economic, socio-political, security and cultural crises. Facing this challenge, each person must be able to push all his/her abilities into competition as the main thing to achieve his/her existence as a human being. To achieve these work goals, people who are competent in carrying out their work or duties are needed. The research aims to see the direct and indirect influence and impact of Covid-19 Pandemic on Organizational Culture and Organizational Commitment of the Employees of Multilevel Marketing Companies in Ambon City. This research is a quantitative, with the research design of a hypothesis testing to examine the effect between variables. The population in this research are all downline members of PT. Cahaya Karunia Persada company in Ambon. The sample in this research uses a saturated sampling technique, because the population are relatively small, which are the uplines of PT. Cahaya Karunia Persada company in Ambon, with a total of 74 people. The coefficient test results show that the Covid-19 pandemic path has a significant and positive effect on organizational culture of 0.943 and an R-Square value of 0.890 (89%), which means that the hypothesis is accepted, since there is a partial positive effect between the COVID-19 pandemic and organizational culture. Similarly, the covid-19 pandemic path coefficient test results have a significant and positive effect on organizational commitment of 0.677 and an R-Square value of 0.458 (45.8%), which means that the hypothesis is accepted, since there is a partial positive effect between the COVID-19 pandemic and organizational commitment.